A wave-based numerical scheme for damage detection and identification in two-dimensional composite structures. (15th April 2019) - Apalowo, R.K.; Chronopoulos, D.
Abstract: Previous studies on wave inspection in different propagation directions have focussed on the analysis of wave propagation and wave scattering from various types of joints in two-dimensional monolayered structures. In this work, a Finite Element (FE) based numerical scheme is presented for quantifying wave interaction with localised structural damage within two-dimensional layered composite structures having arbitrary layering, complexities and material characteristics. The scheme discretises a damaged structural medium into a system of N healthy substructures (waveguides) connected through a joint which bears the localised structural damage/discontinuity. Wave propagation constants along different propagation directions of the substructures are sought by combining Periodic Structure Theory (PST) and the FE method. The damaged joint is modelled using standard FE approach, ensuring joint-substructures mesh conformity. This is coupled to the obtained wave propagation constants in order to determine scattering coefficients for the wave interaction with damage in different propagation directions within the structure. Wave interaction coefficients for different damage types and structural parameters are analysed in order to establish an optimum basis for detecting and identifying damage, as well as assessing the orientation and extent of the detected damage. The main advantage of this scheme is precise predictions at a very low computational cost.